Analysis of Perlocutional Speech Acts on Whatsapp Chat - Tia Fazira; Yusni Khairul Amri (LingLit Journal Scientific Journal for Linguistics and Literature, 2023)
Whatsapp is an internet-based application that has the potential to be used as a medium of communication. The use of WhatsApp itself is simple and does not require a password and is directly connected to contacts and on time to send messages. This analysis aims to describe perlocutionary speech acts contained in whatsapp chat. The data source in this analysis is the man's whatsapp chat. In this analysis, the data were analyzed using perlocutionary speech acts, namely speech acts that refer to the effects that speakers have by saying something, such as making them feel confident, happy and motivated. According to Searle in Chaer (2010: 29-30) types of speech in pragmatics are divided into five namely representative, directive, expressive, commissive, and declaration grouping speech acts into five types, namely representative, directive, expressive, commissive, and declaration speech acts. From the results of the analysis of the twenty data that has been collected, there are 6 data included in the three perlocutionary speech acts, namely 1 directive perlocutionary speech act data (supplication), 2 directive perlocutionary speech act data (confirming), 1 perlocutionary speech act data directive (instructions), 1 data of assertive perlocutionary speech acts (suggesting) and 1 data of expressive perlocutionary acts (quipping).